The Implementation of Pesantren Financing Based on Agribusiness Social Entrepreneurs - Badrudin, Badrudin; Satori, Djam’an; Komariah, Aan; Kurniady, Dedy Achmad (SCAD Independent, 2021)
The sources of pesantren funding are limited either from the government, santri parents, or the community. The government has not budgeted pesantren funds in the state budget or regional budget even though there is a policy for pesantren. The search for pesantren financing sources based on the potential of the agribusiness-based social entrepreneurship environment is very desirable. This article aimed to examine the implementation of pesantren financing based on agribusiness social entrepreneurship. Data collection techniques were carried out with the study of documentation, observation, and interviews with the planning, implementation, supervision, evaluation, and accountability of pesantren financing. The study found that Pesantren Al Ittifak Ciwidey in Bandung District implemented agribusiness-based social entrepreneurship financing through five steps namely planning, implementing, controlling, evaluating, and accountability. The study concluded that the implementation of pesantren financing based on agribusiness social entrepreneurship Al Ittifak Ciwidey Bandung was prepared through accounting (budgeting), namely preparing activity plans and pesantren budgets using SWOT analysis; Funding was carried out to finance underprivileged students, to pay teachers, professional development (training), and infrastructure; Supervision of education funding in PPAI Al Ittifak Ciwidey was carried out by the PPAI Management Team, Kiyai, and the board of educators by monitoring, guiding, and solving problems to the RAPBP, Cash, and Equipment; Funding evaluation was carried out at the end of each semester and the end of the school year. Funding accountability was focused on the parents of students, the community, and the Government as well as the PPAI leader, Kiyai.